MENAKAR EFEKTIVITAS GUGATAN BALIK HARTA BERSAMA DALAM PERKARA KONVENSI PERCERAIAN DI PENGADILAN - Putra Tondi Martu Hasibuan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Counterclaim lawsuit is a manifestation of the implementation of a simple, fast, and low-cost judicial principle. Effectiveness is one of the goals, because both convention and counter-convention lawsuits will be examined and decided together in one decision. In the context of religious courts, joint property disputes can be filed in a reconciliation lawsuit even though the subject matter of the convention lawsuit is divorce. However, the emergence of joint property disputes through the reconciliation lawsuit erodes the main purpose of the existence of the reconciliation lawsuit itself. This research is a normative legal research conducted by examining library materials. In terms of its nature, this research is descriptive-analytic, which is an attempt to collect and compile a data, then analyzed and interpreted. To facilitate understanding, this research uses a normative juridical approach (statute approach). The type of data used is in the form of library materials consisting of primary, secondary, and tertiary legal materials. These data are elaborated and analyzed qualitatively by using inductive method. The result of of this research indicate that the existence of joint property reconvention lawsuits in divorce convention cases is less effective. At the implementation level, there will not be a mediation process, different procedural law, and sociologically it is a trigger for unregistered marriages from the litigants.